Estimation of Genetic Diversity in Progenies of Selected Genotypes of Ulmus villosa Brandis Using Rapd Markers - Thakur, Sapna; Thakur, I. K.; Singh, N. B.; Sharma, J. P.; Sankanur, M. (Indian Forester, 2014)
Molecular diversity among 23 promising progenies of Ulmus villosa, which were raised from the seeds collected from various seed sources in Himachal Pradesh (India), was estimated using 10 RAPD primers. A total of 57 markers were generated, all of the 10 primers showed 100 per cent polymorphism. The similarity coefficient among 23 progenies of U. villosa ranged from 0.00 to 0.70. In which, progeny Jugahan-T3 was found to be the most divergent which separated 3 itself from rest of the progenies at similarity value (0.04) and could be used as a parent in hybridization programme and further improvement programmes. The progenies were grouped into 4 clusters. The cluster II consisted maximum of 12 progenies followed by cluster III (5 progenies), cluster IV (4 progenies) whereas cluster I consisted of single progeny. RAPD analysis proved helpful for estimating the magnitude of genetic diversity at molecular level.